Tradable development rights under uncertainty: An experimental approach - Till Proeger; Lukas Meub; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
Tradable development rights (TDR) are discussed as a mechanism to reduce land consumption while ensuring an efficient implementation of profitable building projects. We present a novel laboratory experiment on the feasibility of TDR and simulate the acquisition and trading of development rights. In particular, we investigate the effects of uncertainty in the revenues of land consumption projects. Overall, we find that TDR are reallocated as suggested by theory, although higher uncertainty has substantial detrimental effects on the distribution of land consumption projects and thus aggregate welfare. This enables us to formulate distinct policy implications for the design of TDR systems.
Keywords: C91; C92; D8; 330; auction; economic experiment; land consumption; tradable planning permits; urban sprawl